Design, synthesis, and pharmacological evaluation of JDTic analogs to examine the significance of the 3- and 4-methyl substituents. Issue 19 (1st October 2015) - Carroll, F. Ivy; Gichinga, Moses G.; Kormos, Chad M.; Maitra, Rangan; Runyon, Scott P.; Thomas, James B.; Mascarella, S. Wayne; Decker, Ann M.; Navarro, Hernán A.
Graphical abstract: Abstract: The design and discovery of JDTic as a potent and selective kappa opioid receptor antagonist used the N -substituted trans -3, 4-dimethyl-4-(3-hydroxyphenyl)piperidine pharmacophore as the lead structure. In order to determine if the 3-methyl or 4-methyl groups were necessary in JDTic and JDTic analogs for antagonistic activity, compounds4a –c, and4d –f which have either the 3-methyl or both the 3- and 4-methyl groups removed, respectively, from JDTic and analogs were synthesized and evaluated for their in vitro opioid receptor antagonist activities using a [ 35 S]GTPγS binding assay. Other ADME properties were also assessed for selected compounds. These studies demonstrated that neither the 3-methyl or 3, 4-dimethyl groups present in JDTic and analogs are required to produce potent and selective κ opioid receptor antagonists.